Phytoremediation of soils contaminated by mine tailings by means of Dactylis glomerata and Pennisetum clandestinum - Vizconde Suárez, Janeth Yvonne (2023)
The tailings of a mining plant in Peru are highly contaminated by heavy metals, containing toxic levels of Al, Cd, Cu, Pb and Zn, presenting a high environmental risk. Therefore, phytoremediation was carried out using Dactylis glomerata and Pennisetum clandestinum on a greenhouse scale for soil recovery. The study was quantitative, explanatory and experimental. Selective sampling and the Interception Line method were used for sampling. The results indicate that the two plant species in soils contaminated with mining tailings have a phytoremediation efficiency by exclusion higher than 99% (p>0.001), immobilizing metals under the non-soluble form. It is concluded that the association of the two species has the root and rhizosphere as the main destination of heavy metals (as undissolved metal), which makes them exclusion phytostabilizing plants.